GAMIFIED MOBILE LEARNING APPLICATIONS: ENHANCING MATHEMATICAL MOTIVATION AND PROBLEM-SOLVING SKILLS IN GRADE 4 STUDENTS - Abdoulaye Diouf; Aissatou Sow; Ousmane Ndiaye (International Journal of Educatio Elementaria and Psychologia, 2025)
The integration of gamified mobile learning applications has gained significant attention in educational settings, particularly in enhancing student motivation and problem-solving skills. In the context of mathematics education, gamification offers the potential to make learning more engaging, interactive, and enjoyable. This study explores the impact of gamified mobile learning applications on mathematical motivation and problem-solving abilities in Grade 4 students. The research aims to determine whether gamification can effectively increase students’ interest in mathematics and improve their ability to solve mathematical problems. A mixed-methods approach was employed, combining pre- and post-test assessments of problem-solving skills, a motivation survey, and classroom observations. The study found that students who used the gamified mobile learning applications exhibited a significant increase in motivation, as well as a notable improvement in problem-solving skills compared to the control group. Students engaged in the gamified environment reported higher levels of enjoyment and confidence in solving math problems. These findings suggest that gamified mobile applications can be an effective tool for enhancing both mathematical motivation and problem-solving abilities. The study concludes that integrating gamification into math education can contribute to fostering a more engaging and effective learning environment, benefiting students’ academic development in mathematics.